Student attitudes and expectations in undergraduate forensic science - Horton, R.; Southam, Daniel; Kelly, Tamsin; Lenehan, C.; Lennard, C.; Lewis, Simon; Lim, K.; Roux, C. (Uniserve Science - University of Sydney, 2012)
Undergraduate forensic science programs in Australia aim to formally educate students in the philosophies, skills and techniques required of practicing forensic scientists. As forensic science is multi-disciplinary, variations in emphasis and foci can result in differences between the curricula of various programs. In order to determine the differences in attributes that our institutions deemed important for students to possess, we collected information from each institutional partner on: the definition of forensic science; methods used to teach forensic science; important knowledge students should acquire from a forensic science-based unit of study or degree program; and the main factors contributing to the retention of students in a forensic science degree program. This feedback was used to develop an instrument to survey students across the various institutions to measure their: perception of popular media as a motivator to study forensic science; personal interest in forensic science; perspective of forensic science as a science; and perspective of forensic science as a profession. This information can be used to relate the diversity of student attitudes and expectations and examine further matters of importance within forensic science education, such as ensuring graduates from various programs are equipped for a career in forensic science.